THE EFFECT OF INTEREST AND FOREIGN EXHANGE RATE ON MACROECONOMIC PERFORMANCE AND BANKING SECTOR - DURMAZ, Assist. Prof. Dr. Yakup; DUSUN, ZeynepDerya; Alsu, Dr. Erkan (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Financial authorities can form economic policies based on the relationship between interest and exchange rates. However, their success on this subject is controversial. In this study, the effect of interest and exchange rates on macroeconomic performance and banking sector will be discussed. The purpose of the study, in this context, is to demonstrate the effects of the relationship between interest and exchange rate. This is really important in terms of revealing the power of financial authorities.